Advanced micromorphology study of microbial films grown on Kefir loaded with Açaí extract. (October 2020) - Matos, Robert S.; Ramos, Glenda Q.; da Fonseca Filho, Henrique D.; Ţălu, Ştefan
Highlights: We successfully obtained microbial films grown on kefir mixed with açaí juice. An advanced micromorphology analysis of the 3D surface of the samples were performed using atomic force microscopy. We determined the stereometric and an advanced fractal analyses of the samples. Fractal analyses revealed a more homogeneous microtexture for the biofilm with 4 % of Açaí. Abstract: In this work, an advanced analysis of the 3D surface microtexture of the microbial films grown on Kefir loaded with Açaí extract was performed. Atomic force microscopy was used to characterize the 3D surface microtexture data in correlation with the stereometric analyses to allow a better understanding of the surface micromorphology consistent with ISO 25178−2: 2012. Two new parameters, fractal succolarity and fractal lacunarity, have been inserted for a quantitative approach to microtexture. The results revealed that the morphology was affected by the increase of the Açaí concentration in biofilms, as well as the fractal succolarity and lacunarity. Adhesive bacteria of the genus Lactobacillus were observed for the lowest concentrations of Açaí. Moreover, it was found that the surface of the biofilms has shown saturation when the concentration has changed from 4 to 6 % of Açaí. These results are of great interest in the characterization of surfaces with promising application like skin dressing.